The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1128/jb.167.3.850-854.1986
|View full text |Cite
|
Sign up to set email alerts
|

Immediate entrance to the export pathway after synthesis as a requirement for export of the sak gene product in Escherichia coli

Abstract: Export through the cytoplasmic membrane and processing of the sak product in Escherichia coli cells were investigated with E. eoli strains carrying pTS301, which produce large amounts of staphylokinase at 42C. High-level synthesis of the sak product caused transient accumulation not only of the staphylokinase precursor (pSAK) but also of the maltose-binding protein and outer membrane protein A precursors. Thus it was concluded that the sak product shares the export pathway with E. coli secreted proteins at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The staphylokinase gene, sak, was isolated from a staphylococcal bacteriophage (32), and the product was shown to be efficiently secreted into the periplasmic space in E. coli by means of its own signal sequence (30). The mechanism of secretion of staphylokinase in E. coli seems to be quite similar to that of endogenous secretory proteins because of its requirement for the secA and prlA (secY) functions (29a).…”
Section: Resultsmentioning
confidence: 99%
“…The staphylokinase gene, sak, was isolated from a staphylococcal bacteriophage (32), and the product was shown to be efficiently secreted into the periplasmic space in E. coli by means of its own signal sequence (30). The mechanism of secretion of staphylokinase in E. coli seems to be quite similar to that of endogenous secretory proteins because of its requirement for the secA and prlA (secY) functions (29a).…”
Section: Resultsmentioning
confidence: 99%
“…However, since a prlA mutant allele which has been isolated as a suppressor of a particular signal peptide mutation can usually suppress many other signal peptide mutations in the same gene and in the other genes at the same time (3,6,23), it is uncertain that the SecY protein directly interacts with a signal peptide. We recently found that export of the staphylokinase (19) from Staphylococcus aureus is blocked in two of the prlA mutant strains examined (the prlA4 and prlA401 strains; Iino and Sako, submitted for publication), although staphylokinase is efficiently exported to the periplasmic space in the wild-type strain (18). Two causes can be proposed for this blockage: (i) the structure of the signal peptide and (ii) an alteration of the SecY protein by the particular prlA mutation.…”
mentioning
confidence: 99%
“…The a-haemolysin produced by some strains seems to be one of the few exceptions [1]. When heterospecific secretable proteins are cloned in E. coli, they are mostly not secreted, and remain in the periplasmic space [1][2][3][4][5][6]. A few cases have recently been reported in which foreign proteins appear to be secreted by E. coli [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%